Haplotypes of the tRNAleu-COII mtDNA Region in Russian Apis mellifera Populations - Milyausha D. Kaskinova; Luisa R. Gaifullina; Elena S. Saltykova (Animals, 2023)
Analysis of the mtDNA tRNAleu-COII locus is a widely used tool to establish belonging to a particular evolutionary lineage of Apis mellifera L. (lineages A, M, C, O, and Y). In Russia, most of the area was once inhabited by Apis mellifera mellifera from the M evolutionary lineage, but the introduction of bee subspecies from the southern regions of Russia (A. m. caucasica, A. m. carnica) and from abroad (A. m. carnica, A. m. ligustica) led to fragmentation of their native range. In this study, the results of assessing the haplotype number for the tRNAleu-COII locus of mtDNA in Russian Apis mellifera populations were presented. We analyzed 269 colonies from 19 regions of Russia. As a result, two evolutionary lineages were identified: the East European lineage C (26.4%) and the Northwestern European lineage M (73.6%). A total of 29 haplotypes were identified, 8 of them were already reported, and 21 were found to be novel. From the C lineage, haplotypes C1, C2, C2c, C2j, and C3 were predominant. All M lineage samples from Russia belong to the M17 and M4’ haplogroups but have only minor variations in the form of nucleotide substitutions. An analysis of publications devoted to the tRNAleu-COII locus haplotypes, as well as an analysis of the available tRNAleu-COII sequences in GenBank, showed that there is still a problem with the haplotype nomenclature.